1988
DOI: 10.1007/bf01851207
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pantothenic acid on fibroblastic cell cultures

Abstract: To evaluate the effects of pantothenic acid during wound healing processes, fibroblastic cell cultures originating from foreskin were established and subcultured by trypsinization. PA (40 micrograms/ml) was added to the basal culture medium. The cell proliferation was estimated by cell count and determination of 3H-thymidine incorporation. The protein synthesis and secretion were determined by dosage in the cells and in the culture medium. When PA was added to the medium, a significant increase of cell prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 9 publications
2
17
0
Order By: Relevance
“…Previous studies [3][4][5][6][7]10], with drastic ex perimental protocols, have shown significant improvement of wound healing process by vitamin supplement, but were carried out either in vitro or on animals. In the present study on humans, important individual varia tions could not be avoided among the numer ous factors involved in the wound healing process, so that one could not hope to obtain massive differences due to vitamin effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies [3][4][5][6][7]10], with drastic ex perimental protocols, have shown significant improvement of wound healing process by vitamin supplement, but were carried out either in vitro or on animals. In the present study on humans, important individual varia tions could not be avoided among the numer ous factors involved in the wound healing process, so that one could not hope to obtain massive differences due to vitamin effects.…”
Section: Discussionmentioning
confidence: 99%
“…AA deficiencies clearly produce alterations of healing processes during scurvy [8]. The sup plement of AA in wound healing processes has been demonstrated by some studies to be efficient, but is still controversial [2,21], PA's effect on wound healing has been rather poorly documented [3,4,6,7], PA is a coenzyme A component and thus involved in energy production processes. In vitro, PA en hances cell growth and intracellular collagen synthesis [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of dexpanthenol on human fibroblasts (e.g. enhanced proliferation, cellular migration, attachment of fibroblasts and collagen synthesis) have been shown in several in vitro studies (14,(53)(54)(55)(56). Although the beneficial influence of dexpanthenol on cell proliferation and wound healing has been well documented, its properties at the molecular level remained unclear for a long time.…”
Section: Part II -Dexpanthenol As Facilitator Of Wound Healingmentioning
confidence: 99%
“…AA enhances in vitro intracellular collagen synthesis [16][17][18], slows down its degradation, and enhances its release out of the cells [ 18], However, some harmful effects (cytostatic ± cytotoxic) caused by AA have already been shown in vitro on fibroblast cultures [19], proving that no valid extrapolation can be made from in vitro experiments. The doses given in this study, although thrice higher than those rou tinely given by clinicians, were 10 times less than doses already given in experimental pro tocols without any side or adverse effects (up to 600 mg/kg/day) [20], On the other hand, AA deficiencies clearly lead to scurvy, a seri ous disease accompanied by the lack of wound healing processes.…”
Section: Ascorbic Acidmentioning
confidence: 99%